Anti-IL-17 Agents in the Treatment of Axial Spondyloarthritis - Atzeni F; Carriero A; Boccassini L; D'Angelo S (ImmunoTargets and Therapy, 2021)
Fabiola Atzeni,1 Antonio Carriero,2,3 Laura Boccassini,4 Salvatore D’Angelo2 1Rheumatology Unit, Department of Clinical and Experimental Medicine, University of Messina, Messina, Italy; 2Rheumatology Institute of Lucania (IReL), Rheumatology Department of Lucania, San Carlo Hospital of Potenza and Madonna delle Grazie Hospital of Matera, Potenza, Italy; 3Translational and Clinical Medicine, Department of Medicine and Health Sciences, University of Molise, Campobasso, Italy; 4Rheumatology Unit, Internal Medicine Department, ASST Fatebenefratelli-Sacco, University School of Medicine, Milan, ItalyCorrespondence: Fabiola AtzeniRheumatology Unit, Department of Clinical and Experimental Medicine, University of Messina, Via C. Valeria 1, Messina, 98100, ItalyTel +39 0902009Fax +39 0902000Email atzenifabiola@hotmail.comAbstract: Axial spondyloarthritis (axSpA) describes a group of chronic inflammatory rheumatic diseases primarily involving the axial skeleton. IL-17 is involved in the pathogenesis of numerous inflammatory diseases, including inflammatory arthritis. Until a few years ago, the only biological agents licensed for the treatment of axSpA and nr-axSpA were TNF inhibitors. However, as some patients did not respond to TNF inhibition or experienced secondary failure, the introduction of the first two IL-17 inhibitors (secukinumab [SEC] and ixekizumab [IXE]) has extended the treatment options, and there are now three others (bimekizumab, brodalumab and netakimab) in various stages of clinical development. The last ten years have seen the development of a number of therapeutic recommendations that aimed at improving the management of axSpA patients. The aim of this narrative review of the published literature concerning the role of IL-17 in the pathogenesis of SpA, and the role of IL-17 inhibitors in the treatment of axSpA, is to provide a comprehensive picture of the clinical efficacy and safety of the drugs themselves, and the treatment strategies recommended in the international guidelines.Keywords: spondyloarthritis, ankylosing spondylitis, non radiographic axial spondyloarthritis, axial spondyloarthritis, anti-TNF drugs, anti-IL17 drugs, interleukin 17